Design of an educational mobile application through app inventor to reinforce the learning process in operations with whole numbers - Quishpe-López, Cristhian (2021)
At present the development and implementation of new technologies has become necessary in all areas, in education it is born with the obligation to use new tools that help to enhance learning. This proposal analyzes an educational mobile application designed on the App Inventor platform, which helps to reinforce the learning process of whole number operations. The ease of use of the free online platform was used to structure all the content in a striking way according to the academic level of the user. Thus, several screens were developed in the application called MatEstudio, each of these screens serves to strengthen the learning process. These screens are made up of theory, simulators, and a game that together help reasoning and knowledge retention. The level of theoretical mathematical knowledge and in Information and Communication Technologies of students of Basic General Education was determined. Subsequently, a survey was applied, in which, based on the results obtained, it was possible to show that there is a problem for the correct understanding of the theory and practice of operations with integers. In this way, it was concluded that it is feasible to implement an Educational App created in App Inventor to reinforce the learning process of operations with numbers.